Effects of Ni doping on the sintering and electrical properties of BaZr0.8Y0.2O3−δ proton conducting electrolyte prepared by Flame Spray Synthesis. Issue 1 (January 2016) - Bozza, Francesco; Bator, Karolina; Kubiak, Wladyslaw W.; Graule, Thomas
Abstract: BaZr0.8 Y0.2 x Ni x O3− δ ( x = 0.01, 0.02) prepared by Flame Spray Synthesis (FSS) were investigated as electrolyte materials for proton conducting fuel cells applications. The as synthesized nanoprecursors, composed of a perovskite phase mixed with doped zirconia and barium nitrate, were sintered at 1400 °C and 1500 °C to form dense specimens. The microstructural and electrical properties of the Ni doped sintered samples were compared with those related to the BaZr0.8 Y0.2 O3− δ sample sintered at 1600 °C. Ni inclusion strongly enhanced densification and grain growth process, reducing the sintering temperature up to 200 °C. AC impedance spectroscopy performed in wet H2 /N2 atmosphere revealed a negative effect of Ni on the proton conductivity. The proton conductivity of 3.8 mS/cm 2 at 450 °C for the BaZr0.8 Y0.18 Ni0.02 O3− δ sample sintered at 1400 °C, associated with the relatively low sintering temperature required, makes of Ni doped BZY20 prepared by FSS a promising electrolyte material for PCFCs working in the intermediate temperature range.